Emergent synthetic methods for the modular advancement of sp3-rich fragments. Issue 13 (9th March 2021) - Caplin, Max J.; Foley, Daniel J.
Abstract : This Perspective reviews recently developed methods that are likely to be of value to the elaboration of sp 3 -rich fragments from carbon-centred vectors, whilst maintaining key fragment-to-target binding interactions. Abstract : Fragment-based drug discovery is an important and increasingly reliable technology for the delivery of clinical candidates. Notably, however, sp 3 -rich fragments are a largely untapped resource in molecular discovery, in part due to the lack of general and suitably robust chemical methods available to aid their development into higher affinity lead and drug compounds. This Perspective describes the challenges associated with developing sp 3 -rich fragments, and succinctly highlights recent advances in C(sp 3 )–H functionalisations of high potential value towards advancing fragment hits by 'growing' functionalised rings and chains from unconventional, carbon-centred vectors.